Guidelines for the calculation of the individual assignment "The analysis of transient processes in the linear electrical circuits" - Rezynkina, M. M.; Kostiukov, I. O.; Lytvynenko, S. A. (National Technical University "Kharkiv Polytechnic Institute", 2022)
These guidelines contain general theoretical provisions concerning the topic: "The analysis of transient processes in the linear electrical circuits", as well as the examples of solutions for the typical problems and the list of the individual assignments. These assignments constitute the basis, which allows the students to gain skills in practical application of theoretical knowledge in the field of the analysis of transient processes in the linear electrical circuits. The necessity of the transient processes analysis is caused by the fact that such analysis allows us to detect various surges of voltage and current, which can lead to the emergencies as well as to damage of the equipment subjected to these surges. Transient processes can also lead to the distortions of signals during their transition through the impulse electronic circuits. The guidelines are intended for the students studying the electrical engineering and computer sciences.
Keywords: guidelines; linear electrical circuits; transient processes; distortions of signals; magnetic field; electrical engineering